Effects of oral sildenafil on exercise capacity in children with pulmonary arterial hypertension: a randomised trial. Issue 2 (3rd December 2019) - Russell, Stuart; Beghetti, Maurice; Oudiz, Ronald; Balagtas, Cecile; Zhang, Min; Ivy, Dunbar
Abstract : Objective: The 16-week, randomised, double-blind Sildenafil in Treatment-Naïve Children, Aged1–17 years, with Pulmonary Arterial Hypertension (STARTS-1) study assessed the effect of sildenafil on cardiopulmonary exercise testing (CPET) in treatment-naïve paediatric patients with pulmonary arterial hypertension (PAH) and included a long-term extension (STARTS-2). CPET has rarely been performed in paediatric patients and we assessed both aerobic capacity with peak oxygen consumption (PVO2 ) and ventilatory inefficiency with the slope of ventilation to carbon dioxide production (VE/VCO2 slope). Methods: Patients (aged 1–17 year) were randomised to low (10 mg), medium (10–40 mg) and high (20–80 mg) sildenafil dose groups. Patients previously treated with placebo in STARTS-1 were randomised to one of three blinded sildenafil dose groups for STARTS-2. CPET was assessed by cycle ergometry at baseline, week 16, and year 1. Results: Of the 234 children randomised, 115 could exercise. At week 16, the combined sildenafil dose group had a 7.7% increase in mean PVO2 percent change from baseline compared with placebo (95% CI −0.2% to 15.6%; p=0.056); at year 1, a significant increase in mean percent change in PVO2 from baseline was only observed in the low-dose group (mean of 12.4% and 95% CI 3% to 21.8%). For VE/VCO2 slope, at week 16, the combined dose group had a −9.7% mean change from baseline compared with placebo (95% CI −14.9% to −4.5%; p<0.001); at year 1, there were no significant changes for any dose group. Conclusions: Sildenafil monotherapy (combined sildenafil dose group) appeared to improve short-term VE/VCO2 slope versus placebo but did not significantly improve PVO2 in treatment-naïve paediatric patients with PAH who were developmentally able to exercise. Trial registration number: NCT00159913 for A1481131, NCT00159874 for A1481156.